INTERTEKSTUALITAS HADIS PEREMPUAN SHALAT BERJAMAAH DI MASJID - Muhammad Habib Zainul Huda (UIN Raden Mas Said Surakarta, 2022)
This paper examines how to understand hadith in a socio-cultural political context. The author takes the example of the hadith,